(untitled) (Zaporizhzhia Historical Review, 2021)
The article analyses numerous factors of everyday cultural consciousness formation which in its turn influences the speciality of inter national relations. Level of routine cultural consciousness acts as something common, consolidating international relationship. The linking factor being household customs, traditions, rites, possessing elements and qualities of human existence and daily life.